23. EVALUATING THE EFFECTIVENESS OF DRUG USE CONSULTATION SOFTWARE FOR CANCER PATIENTS RECEIVING CHEMICAL TREATMENT AT CENTRAL MILITARY HOSPITAL 108 (Vietnam Journal of Community Medicine, 2024)
Objective: The aim of this study is to evaluate the effectiveness of drug consultation software on the counseling activities of clinical pharmacists (CPhs) for chemotherapy-treated cancer patients at 108 Military Central Hospital.Method: A retrospective analysis was conducted on all counseling cases through the drug consultation software at 108 Military Central Hospital from August 1, 2023 to November 15, 2023 and compared with counseling outcomes for cancer patients in the previous period (January 1, 2023 to July 31, 2023).Results: The number of chemotherapy-treated cancer patients counseled by CPhs increased significantly following the implementation of the drug consultation software (a 108% increase). The improvement of knowledge point was evident by the equivalent knowledge assessment scores, rising from 35.7 to 73.3 points/100 points (p < 0.001) before software deployment and from 37.9 to 73.3 points/100 points (p < 0.001) with software assistance. After software implementation, 98.8% of patients evaluated counseling activities as “useful”. All patients assessed counseling by CPhs as “important” with information provided being “adequate”. About 94.2% of patients rated the new counseling format as “satisfied” or “very satisfied”.Conclusion: The support from the drug consultation software has expanded counseling activities for chemotherapy-treated cancer patients, receiving positive and beneficial evaluations from patients. The study results serve as motivation for the hospital to promote and expand the software to enhance counseling effectiveness, thereby improving the quality of treatment.
Keywords: Counselling, cancer, clinical pharmacy, chemotherapy.